The influence of media on impulsive buying in the era of the COVID-19 pandemic - Blažević Bognar, Zrinka; Pleša Puljić, Nikolina (Business, Management and Economics Engineering, 2022)
Purpose – With the appearance of COVID-19, epidemiological measures were implemented which significantly changed the customer behaviour. Media became an important source of information. The fear phenomena in the lockdown era compelled consumers to buy impulsively. Therefore, this paper determines the changes in consumer behaviour in the era of the pandemic and the influence of media on consumer’s impulsive buying during lockdown. Research methodology – The research was carried out with a questionnaire (N = 298). The descriptive, multivariate, and correlation analysis, and the t-test were used to process primary data to confirm changes in consumer behaviour. Findings – The research results show that impulsive buying does exist during a lockdown and is influenced by media. Such indicators give a clear direction for creating marketing campaigns in future crises. Research limitations – The research sample was random so, to prove hypothesis H2, the database of the intensity of buying in lockdown needed to be filtered out so only impulsive buyers could be selected (n = 89). Practical implications – The findings could help in the creation of future marketing campaigns in crises. Originality / Value – This research gives a new look at consumer behaviour in crises, the intensity of fear influence, and the influence of media on consumer behaviour.